Implikasi Hukum Merger Antara Gojek Dan Tokopedia Terhadap Pasar - indra, Rahmadi; Ahmad, Ahmad Rizal Musyafa; Ikarini , Ikarini Dani Widiyanti (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
Gojek Company and Tokopedia official carry out a merger to form one holding company , namely GoTo Group, where is this merger rated potential existence practice competition business no healthy . Journal this aim for analyze opportunity happening competition business no healthy on the Gojek merger and Tokopedia to market . Article this use study juridical normative with the statue approach and the conceptual approach. Results study show existence a opportunity happening competition business no healthy on the Gojek merger and Tokopedia to market . This thing need a analysis with see categorized merger criteria as practice competition business no healthy who has set in Law no. 5 of 1999 concerning practice monopoly and competition business no healthy , there are 3 criteria that is prohibited agreements , prohibited activities and position dominant . Gojek and Tokopedia must open in submission of data regarding mergers, p this aim for guard competition business healthy on the market. However for deciding is the Gojek merger and Tokopedia has violate competition healthy business our must waiting decision from KPPU as institution supervisor competition effort .